Analisis Penerapan Sistem Akuntansi Keuangan dalam Proses Pencatatan dan Pelaporan Keuangan pada PT Afan Logam Lestari Berdasarkan Standar Akuntansi Keuangan (SAK) - Putri Aulia Febriana; Hari Setiono; M. Bahril Ilmiddaviq (Indo Publishing, 2026)
This study analyzes the implementation of the financial accounting system in the recording and financial reporting process at PT Afan Logam Lestari and assesses its conformity with Financial Accounting Standards (SAK). A descriptive qualitative approach was applied. Data were obtained from three purposively selected informants through semi-structured interviews, observation, and documentation. Data analysis involved reduction, data presentation, and conclusion drawing and verification. Data credibility was strengthened through source, technique, and time triangulation and member checking. The findings show that the company operates a semi-manual accounting system supported by Microsoft Excel. Transaction evidence, recapitulation, journalizing, an income statement, and a statement of financial position are available. Nevertheless, the process is not fully integrated, accounting SOPs have not been formally documented, segregation of duties is not yet fully established, and several financial statement components are not presented separately. The study concludes that SAK implementation remains partial. Improvement should prioritize workflow standardization, clearer responsibilities, written SOPs, human resource competence, internal control, and gradual system development according to company needs.